2016
DOI: 10.1016/j.nima.2016.03.084
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cosmic ray muons with spent nuclear fuel dry casks and determination of lower detection limit

Abstract: 27The potential non-proliferation monitoring of spent nuclear fuel sealed in dry casks 28 interacting continuously with the naturally generated cosmic ray muons is investigated. 29 Treatments on the muon RMS scattering angle by Moliere, Highland and, 30 Lynch-Dahl were analyzed and compared with simplified Monte Carlo simulations. The 31Lynch-Dahl expression has the lowest error and appears to be appropriate when performing 32 conceptual calculations for high-Z, thick targets such as dry casks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…Simulations with 10 6 muons with energy in the range 1-60 GeV result in scattering variance estimates for a vertical fully loaded dry cask, a half loaded and an empty one are 4119.453, 2792.103 and 1493.074 mrad 2 , respectively. The scattering variance distribution is shown to follow Gamma distribution and its moments can be derived as shown in [30]. Then, using…”
Section: A Muon-dry Cask Interactionsmentioning
confidence: 99%
“…Simulations with 10 6 muons with energy in the range 1-60 GeV result in scattering variance estimates for a vertical fully loaded dry cask, a half loaded and an empty one are 4119.453, 2792.103 and 1493.074 mrad 2 , respectively. The scattering variance distribution is shown to follow Gamma distribution and its moments can be derived as shown in [30]. Then, using…”
Section: A Muon-dry Cask Interactionsmentioning
confidence: 99%
“…Recently, the use of muons in nuclear nonproliferation and safeguards verification applications has received attention as a passive and penetrating way to interrogate objects. This endeavor has been assisted by the development of detectors that can measure and provide information related to the incoming and outgoing trajectories of individual muons [2][3][4][5][6]. Recently, cosmic ray muons have been investigated for volcano imaging [7][8][9] and cargo scanning applications [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cosmic ray muons have been investigated for volcano imaging [7][8][9] and cargo scanning applications [10][11][12]. Their use has been extended to nuclear waste imaging [13][14][15][16] and determination of nuclear fuel debris location in nuclear reactors having suffered from the effects of a severe accident such as the one that occurred in Fukushima [17,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conventional active radiography with neutrons or photons is not feasible due to the heavy shielding that is used to contain the radiation emitted by the fuel, as well as self-shielding from the fuel assemblies themselves, which can total over 100 radiation lengths for typical casks [14]. Previous work showed that measurements of radiation which escapes the cask are capable of proving that the cask has radioactive contents, but the scattered radiation which emerges does not carry sufficient radiographic information to determine if individual assemblies are missing [15].…”
Section: Introductionmentioning
confidence: 99%